Significant genetic heterogeneity of the SIVmac251 viral swarm derived from different sources. - Strickland, S; Gray, R; Lamers, S; Burdo, T; Huenink, E; Nolan, D; Nowlin, B; Alvarez, X; Midkiff, C; Goodenow, M; Williams, K; Salemi, M (2011)
Infecting rhesus macaques (Macaca mulatta) with the simian immunodeficiency virus (SIV) is an established animal model of human immunodeficiency virus (HIV) pathogenesis. Many studies have used various derivatives of the SIVmac251 viral swarm to investigate several aspects of the disease, including transmission, progression, response to vaccination, and SIV/HIV-associated neurological disorders. However, the lack of standardization of the infecting inoculum complicates comparative analyses. We investigated the genetic diversity and phylogenetic relationships of the 1991 animal-titered SIVmac251 swarm, the peripheral blood mononuclear cell (PBMC) passaged SIVmac251, and additional SIVmac251 sequences derived over the past 20 years. Significant sequence divergence and diversity were evident among the different viral sources. This finding highlights the importance of characterizing the exact source and genetic makeup of the infecting inoculum to achieve controlled experimental conditions and enable meaningful comparisons across studies.